The Molecular Structure and Role of Humanin in Neural and Skeletal Diseases, and in Tissue Regeneration - Zhu, Sipin; Hu, Xiaoyong; Bennett, Samuel; Xu, Jiake; Mai, Yuliang (Frontiers in Cell and Developmental Biology, 2022)
Humanin (HN) belongs to a member of mitochondrial-derived peptides (MDPs) which are encoded by mitochondrial genes. HN shares sequence homology with thirteen HN-like proteins, named MTRNR2L1 to MTRNR2L13, which encompass 24 to 28 amino acid residues in length. HN mediates mitochondrial status and cell survival by acting via an intracellular mechanism, or as a secreted factor via extracellular signals. Intracellularly, it binds Bcl2-associated X protein (BAX), Bim and tBid and IGFBP3 to inhibit caspase activity and cell apoptosis. When released from cells as a secreted peptide, HN interacts with G protein-coupled formyl peptide receptor-like 1 (FPRL1/2) to mediate apoptosis signal-regulating kinase (ASK) and c-Jun N-terminal kinase (JNK) signalling pathways. Additionally, it interacts with CNTFR-α/gp130/WSX-1 trimeric receptors to induce JAK2/STA3 signalling cascades. HN also binds soluble extracellular proteins such as VSTM2L and IGFBP3 to modulate cytoprotection. It is reported that HN plays a role in neuronal disorders such as Alzheimer’s disease, as well as in diabetes mellitus, infertility, and cardiac diseases. Its roles in the skeletal system are emerging, where it appears to be involved with the regulation of osteoclasts, osteoblasts, and chondrocytes. Understanding the molecular structure and role of HN in neural and skeletal diseases is vital to the application of HN in tissue regeneration.